Komparasi Hak Waris Pada Anak Adopsi Dalam Perspektif Hukum Islam Dan Hukum Perdata - Mahesa Arya Pratama; Yosua Parulian Pardede; Jesika Bonita Sibarani; Intan Gloria Mawar Silangit (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study examines the comparison of inheritance rights of adopted children from the perspective of Islamic law and civil law in Indonesia. The background of the research is the importance of a clear understanding of the legal status of adopted children, given the growing number of couples adopting children because of the inability to have children. The aim of this study is to explain and compare the inheritance rights of adopted children in both legal systems. The method used is normative research with legislative approaches, examining regulations, laws and related regulations. The results of research show that in Islamic law, the adopted child is not entitled to inherit property from the foster parent because there is no national relationship, but can be given property through a will with a maximum of 1/3 of the inheritance. The implications of these findings are the need for harmonization of laws and policies that can provide legal certainty and justice for adopted children in Indonesia, accommodating the differences between the two legal systems.